Are They Efficient in the Middle? Using Propensity Score Estimation for Modeling Middlemen in Indian Corporate Corruption - Biswas, Malay (Journal of business ethics, 2017)
Corrupt regulatory environment encourages firms to deploy middlemen for speedy and assured acquisition of different services from regulatory agencies. Using a World Bank dataset of 2210 Indian manufacturing firms, this article examines how firms with middlemen deal with corrupt governmental agencies for its operational efficiency. Our results demonstrate that deployment of middlemen by the firms is often accompanied by a substantial increase in operational delay, relatively trigger more consumption of senior management’s time on regulatory disentanglement, enhance the likelihood/tendency to pay bribe, and likely to face more court cases as a means of restitution of legal rights. As firm-specific attributes may contaminate our preliminary results, we utilized the propensity score framework to examine relationships among variables of interests. Our study contributes to the inconspicuous part of the corruption literature by attempting to present a comprehensive but indirect assessment of the functions of middlemen that predominantly remained unattended except some scattered descriptive, case-based anecdotal presentations.